Indução, isolamento e caracterização de linhagens de calos de feijão-de-corda (Vigna unguiculata). - Jereissati, Emmanuel de Sousa (2008)
Somatic embryogenesis is the process by which somatic plant tissues gives rise to plant embryos under inductors conditions. Somatic embryogenesis represents the most commonly employed tool in commercial propagation of plants. In recent times, genes involved in the process have been identified, partucularly those involved in the maintenance of meristems and pattern formation. There are genes which, when ectopically expressed, can induce the formation of somatic embryos. In cowpea, there are few reports on somatic embryogenesis. In addition, the reports on the process recorded a very low frequency and a complicated system of regeneration involving several steps. This work attempted to isolate callus lines of cowpea and establish an ideal culture condition necessary for their maintenance. Histological analysis was conducted to characterize the isolated lines of callus anatomically. From the four lines obtained, 3 presented cells exhibiting the charactersitc embryogenic potential and of this, Line 2 actually gave rise to embryogenic structures when cultured in liquid media. The lines of callus were maintained in cultured condition for over a year without loss of their characteristics. Experiments that monitored the growth of cell suspension from the callus revealed that five days is the best period for subculture of the cells. Regeneration experiments in cowpea will find the different callus lines isolated in this work useful in the attempt to optimize the different strategies of regeneration of the crop in vitro.